(untitled) (Annals of Medical Research, 2022)
Aim: Dynapenia (D) and abdominal obesity (AO) are associated with many adverse health outcomes in the elderly. In our study, we aimed to evaluate the role of dynapenia and abdominal obesity in determining the risk of falling in the elderly. Materials and Methods: A total of 400 (71.6±5.9) elderly, 228 of whom were women, were included in the study. All participants were evaluated with anthropometric measurements as well as hand grip strength, gait speed and Tinetti Balance and Gait Assesment (TBGA). AO was defined by waist circumference (WC) (WC≥102 cm in men and WC≥88 cm in women). Hand grip strength (HGS) was measured by hand dynamometry. Those with HGS <27 kg for men and <16 kg for women were defined as dineapenic (D). All participants were classified as ND/NAO, D/NAO, ND/AO, and D/AO. Results: Gait speed was found to be lower in the ND/AO and D/AO groups (p<0.001). According to TBGA scores, 25 (35.2%) of 71 patients with high fall risk were D/AO, while 27 (38%) were ND/AO (p=0.018). While the risk of high falls was 14.4% in the ND/AO group, this rate increased to 24% in the D/AO group. WC (p<0.001, OR= -0.01 [-0.01-0.01]), HGS (p=0.025, OR= 0.03 [0.00-0.01]) and TBGA (p<0.001, OR= 0.066 [0.06-0.07]) high were determined as predictors of fall risk. Conclusion: Our study showed that WC and HGS measurements, as well as TBGA, are effective in detecting high fall risk in the elderly. It may be possible to prevent falls and fall-related injuries by early detection of abdominal obesity and decreased muscle strength, which are among the correctable risk factors in the elderly, and by performing the necessary interventions.